Prediction of success of induction of labour: Bishop’s score versus transvaginal sonographic parameters - Dasari, Papa; Thiyagalingam, Sutharshika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Bishop’s score is a standard method of pre-induction assessment of parameters to predict induction of labour. It is subjective and has interobserver variability and it does not take in to account the supra-vaginal cervix which forms more than 50% of cervical length. During the past 3 decades studies undertaken to find out a better predictor of labour induction found ultrasonographic assessment of cervix to be a better method. Cervical length, posterior cervical angle and head position are some of the parameters that were studied and compared with Bishops score. Among these posterior cervical angles of >1100 and cervical length of <2 cm are the best predictors for success of induction of labour. These parameters would help to explain the chances of vaginal delivery and the risk of undergoing caesarean section in an objective way.